Experience with double transposition flaps and intravelar veloplasty for closure of wide cleft palates - Pavan Venkateswar Kolisetty; Sheikh Sarfraz Ali; Indrajith K Sudhy (Wolters Kluwer Medknow Publications, 2024)
Background: Repairing a wide cleft palate is a challenging task for surgeons. The goals of cleft palate repair such as achieving anatomical closure of the defect, complete velopharyngeal closure, speech development, and to minimize dentoalveolar anomalies are difficult to achieve in wide and massive cleft palates. Several methods have been described for the same. We performed double transposition flaps combined with intravelar veloplasty in our patients. In this article, we share our experience with the same. Materials and Methods: We reviewed 9 cases, in which double transposition flaps with intravelar veloplasty were performed. Patient demographics, clinical data, and outcomes were analyzed. Functional status including nasal resonance and palatal mobility were assessed with nasal endoscopy. Results: The average age at the time of surgery was 17 months. Four patients had associated diseases. The mean operative time was 55.7 min. The mean follow-up period is 23.7 months. Only posterior palatal closure was done in all the cases and patients were managed temporarily with obturators and are planned for delayed closure later. Conclusion: Double transposition flap is a safe, effective, and technically less demanding procedure. It has no wound complications and can avoid the need for osteotomy to correct maxillary retrusion. The main drawback of the procedure is the creation of an anterior palatal fistula that needs closure later.